2012
DOI: 10.1017/s0007114512000682
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic and lifestyle determinants of ‘Western-like’ and ‘Health conscious’ dietary patterns in toddlers

Abstract: Determinants of a child's diet shortly after weaning and lactation have been relatively understudied. The aim of the present study was hence to identify common dietary patterns in toddlers and to explore parental and child indicators of these dietary patterns. The study was a population-based, prospective birth-cohort study in Rotterdam, the Netherlands. Food consumption data of 2420 children aged 14 months were used. A 'Health conscious' dietary pattern characterised by pasta, fruits, vegetables, oils, legume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
131
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 99 publications
(150 citation statements)
references
References 41 publications
16
131
3
Order By: Relevance
“…15,20 Infant' s gender, gestational age and birth weight were obtained from obstetric records assessed in midwife practices and hospital registries. 14 Information about maternal age, maternal BMI, parity, educational level, ethnicity, marital status, household income, and any family history of asthma, eczema, allergy to house dust, or hay fever was obtained by questionnaire at enrollment.…”
Section: Covariatesmentioning
confidence: 99%
See 1 more Smart Citation
“…15,20 Infant' s gender, gestational age and birth weight were obtained from obstetric records assessed in midwife practices and hospital registries. 14 Information about maternal age, maternal BMI, parity, educational level, ethnicity, marital status, household income, and any family history of asthma, eczema, allergy to house dust, or hay fever was obtained by questionnaire at enrollment.…”
Section: Covariatesmentioning
confidence: 99%
“…15 Questions from the FFQ on the consumption fish are found in Supplemental Table 6. We divided the fish products into 2 groups on the basis of their fat content: (1) fatty fish defined as .10 g fat per 100 g: herring, mackerel, eel, and salmon; (2) other fish defined as 0 to 10 g fat per 100 g: white fish, fish fingers, squid, flounder, cod, pollack, haddock, tilapia, sole, tuna, whiting, trout, gurnard, perch, plaice, wolf fish, and swordfish.…”
Section: Timing Of the Introduction Of Fish And Amount Of Fish Consummentioning
confidence: 99%
“…Instead, we used dietary n-3 and n-6 intake during infancy, as assessed by a 211-item Food Frequency Questionnaire when children were 14 mo old (30). N-3 and n-6 intake were adjusted for total energy intake using the residual method (31) and were available for 2,785 of the children in the current study sample.…”
mentioning
confidence: 99%
“…Assessing the relationship between food consumption and per capita income, it was found that families with higher incomes had a lower consumption of manufactured goods in relation to families with income below half a minimum wage per capita. The data found by Jong et al [26] shows that family income influences on the type of foods' pattern. According to the authors, children of lower incomes had high adherence to unhealthy food patterns.…”
Section: Discussionmentioning
confidence: 94%